2005
DOI: 10.2527/2005.83122752x
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate, body composition, and meat tenderness in early vs. traditionally weaned beef calves1,2

Abstract: One hundred forty spring-born Angus x Gelbvieh and purebred Angus steers were selected for study as early weaned (EW; average age at weaning = 90 +/- 30 d) or traditionally weaned (TW; average age at weaning = 174 +/- 37 d) steers that were non-implanted or implanted (Synovex-S, Fort Dodge Animal Health, Overland Park, KS). Initially, steers were sorted by age, sire, and farm, and then allotted randomly in a 2 x 2 factorial arrangement of treatments of EW implanted (EWI), EW nonimplanted (EWN), TW implanted (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 21 publications
8
34
2
Order By: Relevance
“…Early-weaned calves had heavier carcasses with a concomitant improvement of dressing percentage and fatness score, as had already been reported in other studies (Fluharty et al, 2000;Meyer et al, 2005;Blanco et al, 2007). However, Fluharty et al (2000) also reported an improvement of carcass grade with early weaning, which did not appear in the current study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Early-weaned calves had heavier carcasses with a concomitant improvement of dressing percentage and fatness score, as had already been reported in other studies (Fluharty et al, 2000;Meyer et al, 2005;Blanco et al, 2007). However, Fluharty et al (2000) also reported an improvement of carcass grade with early weaning, which did not appear in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…The fact that early-weaned calves, being already adapted to intensive feeding, had higher intakes than traditionally weaned calves during the first month of the finishing phase had already been reported (Fluharty et al, 2000;Meyer et al, 2005). The studies cited above also reported a higher intake of traditionally weaned steers in the second to fourth month of the finishing phase, although in the current study differences were only significant during the third month.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Alternative beef production systems, including reducing age at slaughter, may result in younger, higher marbled beef, but with lower carcass weights and smaller steak portion size (Schoonmaker et al, 2002). However, the effects on meat tenderness have been inconsistent (Klopfenstein et al, 2000;Schoonmaker et al, 2002;Meyer et al, 2005). Anabolic implants are used in the beef industry to improve growth rates and feed efficiency during finishing.…”
Section: Introductionmentioning
confidence: 99%
“…Weaning at 30 to 45 days [3] or 80 to 150 days postpartum [2,4,5] improved efficiency and was economical [3] when forage quality and/or quantity were inadequate. Early-weaned calves gained more efficiently and yielded greater quality USDA grades than traditionally weaned calves [6,7] at finishing [8,9].…”
Section: Introductionmentioning
confidence: 99%